2022
DOI: 10.1039/d2nr02712g
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic viscosity of methane hydrate systems from non-Einsteinian, plasma-functionalized carbon nanotube nanofluids

Abstract: The viscosity of oxygen-functionalized multi-walled carbon nanotube (O-MWCNT) nanofluids was measured for concentrations from 0.1 to 10 ppm under conditions of 0 to 30 MPag pressures and 0 to 10...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The reference water system has been tested under a 400 s –1 shear rate, a typical value for the measuring system to register accurate readings with low-viscosity, aqueous samples. A much lower shear rate of 80 s –1 was also tested in the current study to verify the hypothesis of whether 400 s –1 would inhibit the formation of critical hydrate clusters, as suggested in the previous reports . Measurements were averaged over a full revolution (AOFR) with an adjustment time of 5 s for nonhydrate runs and 1 s for hydrate-forming runs.…”
Section: Methodsmentioning
confidence: 80%
“…The reference water system has been tested under a 400 s –1 shear rate, a typical value for the measuring system to register accurate readings with low-viscosity, aqueous samples. A much lower shear rate of 80 s –1 was also tested in the current study to verify the hypothesis of whether 400 s –1 would inhibit the formation of critical hydrate clusters, as suggested in the previous reports . Measurements were averaged over a full revolution (AOFR) with an adjustment time of 5 s for nonhydrate runs and 1 s for hydrate-forming runs.…”
Section: Methodsmentioning
confidence: 80%
“…However, the experimental limitations (kinetic, mass diffusion, and heat effects) of working with gas hydrates in shear rheometers that reduce the feasibility of such rheological work have also been identified [ 30 ]. Moreover, the addition of plasma-functionalized carbon nanotube nanofluid promoters to methane hydrate systems has been reported, suggesting molecular scale phenomena as a cause of non-Einsteinian dynamic viscosity effects [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive list of best practices for the calculation of transport properties by molecular dynamics has been compiled by Maginn et al [ 42 ]. The computational estimation of the transport properties of pre-nucleation methane hydrate systems via MD is a promising alternative to overcome the limitations in the experimental rheology work of gas hydrates [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have also been many recent studies on the viscosity of graphene and graphene oxide nanofluids. This is the first time the viscosity of plasma-functionalized graphene has been measured in any system, including liquid and hydrate systems. Though other nanofluids have been analyzed at similar pressures, evaluating the viscosity of graphene nanofluids at high pressure is also entirely novel. Additionally, this study is paired with another publication that used oxygen-functionalized multiwalled carbon nanotubes in similar systems . A comparison between these two studies is found in that study and will not be further referenced here.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] Additionally, this study is paired with another publication which used oxygen-functionalized multi-walled carbon nanotubes in similar systems. 40 A comparison between these two studies is found in that study and will not be further referenced here.…”
Section: Introductionmentioning
confidence: 99%